Futuristic perception on critical thinking in the new era (Revista Innova Educación, 2021)
Children from an early age must acquire superior abilities, which serve as the basis for their life. This study seeks to understand the perception of the most notable aspects of critical thinking in the current era, with a look towards the future. An exhaustive review, observation, selection, and collection of information of the most relevant scientific articles published in recent years were carried out through documentary analysis. In addition, the search for reliable databases, both national and foreign, was used. Critical thinking was found to have a path of historical notableness in humanity. In addition, the current situation of the pandemic makes it possible to show the need to leave futuristic life lessons so as not to be overwhelmed or relegated to the past. It is the ability to reinvent yourself an option to provide solutions to possible adverse situations.
Keywords: teachers; strategies; critical thinking; TICs